Attitude and Performance of Nurses in Oral Care in Intensive Care Unit Patients - Elham Niknejad (Journal of Global Pharma Technology, 2017)
Introduction: Prevention of respiratory tract infections in intensive care units is an important aspect of patient safety and oral care as nursing intervention plays an important role in reducing the risk of infection so the present study was aimed to determine attitude and performance of nurses in oral care in intensive care unit patients. Materials and Methods A descriptive study in which105nurses working in special educational- therapeutic centers affiliated to Uremia University of Medical Sciences were selected by available sampling method. For data collection a part of rello et al. questionnaire was used. Data analysis was performed using descriptive statistics and Chi-square test. Results showed that the majority of nurses (87.5% and72.8%), respectively had moderate attitude and performance about their oral care, but based on chi-square tests there is no significant relationship between attitude and performance of the staff. The majority of nurses (85.3%) are not using protocol and the standard tool for the assessment of oral healthcare. Conclusion Education of basic concepts of health care is necessary in order to enhance employee attitude and performance and improve the patient's status in intensive care units and should be taken into consideration by the authorities’ and directors of nursing.Keywords: Attitude, Performance, Nurses, Oral Care, Intensive care unit.